BURBANKITE GROUP MINERALS AND THEIR ALTERATION IN RARE EARTH CARBONATITES-SOURCE OF ELEMENTS AND FLUIDS (EVIDENCE FROM C-O AND SR-ND ISOTOPIC DATA) - Zaitsev A.N.; Demény A.; Sindern S.; Wall F. (My University, 2002)
The 370–380 Ma Khibina and Vuoriyarvi complexes on the Kola Peninsula, Russia, which form part of the Palaeozoic Kola Alkaline Province, contain REE-rich carbonatites with burbankite (Na,Ca)3(Sr,Ca,REE,Ba)3(CO3)5 or calcioburbankite (Na,Ca)3(Ca,Sr,REE,Ba)3(CO3)5 as the principal primary REE mineral. Within each complex the C–O and Sr–Nd isotopic data are similar for burbankite group minerals and co-existing calcite or dolomite (Khibina: δ13C(V-PDB)=−6.4 to−5.8‰, δ18O(V-SMOW)=7.3–7.7‰, (87Sr/86Sr)370=0.70390–0.70404 and (143Nd/144Nd)370=0.51230–0.51235; Vuoriyarvi: δ13C=−4.2 to −3.0‰, δ18O=8.1–9.4‰, (87Sr/86Sr)370=0.70313–0.70315 and (143Nd/144Nd)370=0.51243–0.51245). This indicates that the REE mineralization and its host carbonatites in each complex are derived from the same source and are co-genetic. There is, however, a great difference between the Sr, Nd and C isotopic signatures from Khibina and Vuoriyarvi, whereas the δ18O ranges are similar. This suggests that the REE carbonatites of the two complexes originate from sources with different isotopic signatures. At least three mantle components are needed to explain the variations in Sr and Nd compositions in the carbonatites from Kola. The δ13C ranges of primary carbonatites with low δ18O values are quite different for Khibina and Vuoriyarvi and show correlation with the radiogenic isotope compositions. The data may be best explained by subduction-related source contamination that caused δ13C variations in different mantle components. During late-stage processes burbankite and calcioburbankite have been replaced by various assemblages of REE–Sr–Ba minerals. The alteration of burbankite group minerals is an open-system hydrothermal process leading to multiple element transfer. It has produced mineral assemblages which are characterized by high δ18O values (Khibina: δ18O(V-SMOW)=11.4–13.9‰ and Vuoriyarvi: δ18O=17.1–18.0‰) compared to primary burbankite and calcioburbankite. Co-existing calcite and dolomite have retained their original C and O isotope compositions, and one calcite sample from Khibina shows strong positive δ13C–δ18O shifts similar to those of the pseudomorph. The high δ18O and sometimes high δ13C values can be attributed to low-temperature isotope exchange between minerals and fluid with variable CO2/H2O ratio taking place during and/or after crystallization as usually observed in carbonatites. The Sr and Nd isotope compositions of pseudomorphs and associated calcite/dolomite in general are identical to those of burbankite/calcioburbankite and associated carbonates suggesting that the fluids which caused burbankite alteration are from the same source, i.e. carbonatitic. Small variations in the Sr and Nd isotope signatures point to interaction of the pseudomorph-forming fluid with alkali silicate wall rocks.
Keywords: Burbankite; Calcioburbankite; Pseudomorph; Carbonatite; C–O–Sr–Nd isotopes; Kola Alkaline Province